The influence of farmers' knowledge of the jajar legowo planting system on rice production - Pebriana, Rianti; Kurniati, Dewi; Oktoriana, Shenny (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2025)
The Legowo row planting system is a method of rice cultivation with several rows separated by one empty row. This research aims to determine the influence of farmers' knowledge and skills in applying the Legowo row planting system on rice production. A quantitative descriptive method was used with 112 rice farmers who have implemented the system in Landak Regency. Data analysis was performed using the structural equation modeling (SEM) model with SMART PLS 3.0 software. The results show that rice production using the Legowo planting system is significantly influenced by knowledge factors, including training levels and innovation adoption, and skill factors, including procedures and water management. These factors significantly impact rice production for farmers implementing the Legowo system.